Age of initiation, psychopathology, and other substance use are associated with time to use disorder diagnosis in persons using opioids nonmedically. Issue 4 (2nd October 2017) - Schepis, Ty S.; Hakes, Jahn K.
ABSTRACT: Background : Nonmedical use of prescription opioids (NMUPO) is an ongoing public health challenge, as NMUPO is associated with psychopathology, other drug use, and fatal overdose. These concomitant risks are greatest in those with opioid use disorder (OUD), but the development of NMUPO-related use disorder is poorly understood. The primary aim of this study was to establish factors associated with the development of and time to OUD among persons engaged in NMUPO. Methods : Data were from wave 1 of the National Epidemiologic Study on Alcohol and Related Conditions, with 1755 participants endorsing lifetime NMUPO. Analyses used sequential design-based logistic regression for DSM-IV ( Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition ) opioid dependence correlates, followed by Cox regression of proportional hazards for correlates (e.g., sociodemographics, age of NMUPO initiation, and psychopathology) of time to dependence in those who developed DSM-IV dependence. Results : Earlier age of NMUPO initiation increased OUD odds (adjusted odds ratio [AOR] = 0.95, 95% confidence interval [CI] = 0.94–0.96) but slowed OUD development (adjusted hazard ratio [AHR] = 1.05, 95% CI = 1.04–1.06) in those who developed OUD ( n = 118), after controlling for sociodemographics, psychopathology, and ages of other drug use initiation. Psychopathology and earlier other drug use initiation were associated with higher OUD odds, but only having an alcohol use disorder was associated with shorter time to OUD. Conclusions : Earlier NMUPO initiation is associated with increased odds of OUD, although those with early initiation had a slower progression to OUD. Programs that prevent early NMUPO initiation, which might lower rates of OUD, and/or identify the later initiators at highest risk for rapid OUD development could have great public health benefits.